Effect of antagonists on the induction of systemic resistance with defense related enzymes in sugarcane against red rot disease - Sangeetha, A.; Neelamegam, R.; Mohan, S. (Indian Phytopathology, 2011)
Six months old sugarcane plants were treated with microbial antagonists like Pseudomonas fluorescens, Trichoderma viride, T. harzianum, Gliocladium virens and Bacillus subtilis by soil application and challenged with Colletotrichum falcatum inoculation by bore-hole method to evaluate the induction of systemic resistance with defense related enzymes (Peroxidase, Polyphenol oxidase and Phenylalanine ammonia-lyase) and total phenol content in sugarcane against red rot disease. In general the enzyme activities were on higher side when sugarcane plants were treated with antagonists compared to control (healthy) and pathogen inoculated check. In the present investigation, it was observed that the sugarcane plants applied with T. viride, T. harzianum, P. fluorescense and G. virens significantly induced the defense compounds (peroxidase and polyphenol oxidase) compared to unsprayed control. Application of P. fluorescens increased the activities of peroxidase, polyphenoloxidase, phenylalanine ammonia lyase and enhanced the accumulation of phenols in sugarcane plants on challenge inoculation with C. falcatum.